The Evolution of Defects in Zirconium in the Process of Hydrogen Sorption and Desorption; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Laptev R. S. Roman Sergeevich; Lider A. M. Andrey Markovich; Bordulev Yu. S. Yuri Sergeevich; Kudiyarov V. N. Victor Nikolaevich; Gvozdyakov D. V. Dmitry Vasilievich (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen